Eileen - Moshfegh, Ottessa 1981- (Penguin Press, 2015)
Dreaming of life in the city while caring for her alcoholic father and working in a 1960s boys' prison, a disturbed young woman is manipulated into committing a psychologically charged crime during the holiday season
Keywords: Prisons / Fiction; Fathers and daughters / Fiction; Fiktionale Darstellung